2023
DOI: 10.1177/10901981231178696
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Tobacco Use Patterns Among Adults in the United States: Exploring sex differences

Abstract: Objective Adverse childhood experiences (ACEs), which refer to childhood traumatic events, have been identified as risk factors for tobacco use in adulthood. However, studies are limited on the effect of sex on the association of ACEs with e-cigarettes and dual use of e-cigarettes and cigarettes. This study explored sex differences in the association of ACEs with e-cigarettes, cigarettes, and dual use of e-cigarettes and cigarettes among adults in the United States. Methods This was a cross-sectional analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Specifically, as the number of ACEs increased, the odds of engaging in current e-cigarette use also increased. Another study that used 2020 BRFSS data and included a wide range of adults reported similar findings, and also noted that there were varying strengths of associations by participants' sex with female adults having higher odds of ecigarette use whereas male adults had higher odds of cigarette smoking and dual e-cigarette and cigarette use [32]. Additionally, an Australian study also suggested a dose-response association between the cumulative number of ACEs and lifetime or past-year e-cigarette use [40].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Specifically, as the number of ACEs increased, the odds of engaging in current e-cigarette use also increased. Another study that used 2020 BRFSS data and included a wide range of adults reported similar findings, and also noted that there were varying strengths of associations by participants' sex with female adults having higher odds of ecigarette use whereas male adults had higher odds of cigarette smoking and dual e-cigarette and cigarette use [32]. Additionally, an Australian study also suggested a dose-response association between the cumulative number of ACEs and lifetime or past-year e-cigarette use [40].…”
Section: Discussionmentioning
confidence: 70%
“…Other research has examined ACEs as predictors of e-cigarette use among a wide age range of adults living in one U.S. state, Florida, and found that a higher cumulative number of ACEs (i.e., ≥4) is associated with current e-cigarette use [31]. Another study assessed the potential effect of sex on the association of ACEs and current e-cigarette and cigarette smoking patterns among U.S. adults of all ages, and reported that there was no interaction by sex, but a higher cumulative number of ACEs (i.e., ≥4) was associated with use [32]. More research is needed to assess this association among a national sample of young adults living across the U.S.…”
Section: Introductionmentioning
confidence: 99%